Monitoring of Zn and Cr in Downstream Water from Uzuncayir Dam in Turkey - Topal, M.; Topal, Arslan E., I (Univ Tehran, 2019)
In this study, the concentrations of Zn and Cr in downstream waters from Uzuncayir Dam (Tunceli, Turkey) were monitored during spring (March, April, May) and summer (June, July, August) season. Zinc and Cr concentrations in surface water samples were detected using the ICP-MS device. According to the data obtained the lowest Zn and Cr concentrations in the spring season were 65.43 +/- 3.2 mu g/L in March at 10th day for Zn and 0.28 +/- 0.02 mu g/L in March at 10th and 20th day for Cr, the highest Zn and Cr concentrations were determined to be 83.12 +/- 4.1 mu g/L in May at day 30 for Zn and 0.48 +/- 0.02 mu g/L in May at day 30 for Cr. The lowest Zn and Cr concentrations in summer season were 55.48 +/- 2.7 mu g/L at 30th day in August for Zn and 0.54 +/- 0.03 mu g/L at 10th day in June for Cr. The highest Zn and Cr concentration in summer season were found as 69.48 +/- 3.5 mu g/L in June at day 10 for Zn and 1.23 +/- 0.06 mu g/L in August at day 30 for Cr. The Zn and Cr concentrations in the downstream of Uzuncayir Dam were found to be smaller than the Zn and Cr concentrations given by the Surface Water Quality Regulation (SWQR). As a result, it was determined that there was no harm in using water from the Uzuncayir Dam as irrigation water or drinking water in terms of Zn and Cr concentrations.
Keywords: Downstream; monitoring; water quality; Tunceli; Turkey